1977
DOI: 10.1083/jcb.72.2.292
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of a periodic protein layer in the outer membrane of Escherichia coli.

Abstract: Matrix protein (36,500 daltons), one of the major polypeptides of the Escherichia coli cell envelope, is arranged in a periodic monolayer which covers the outer surface of the peptidoglycan. Although its association with the peptidoglycan layer is probably tight, the periodic structure is maintained in the absence of peptidoglycan, and is therefore based on strong protein-protein interactions. A detailed analysis of the ultrastructure of the matrix protein array by electron microscopy and image processing of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(46 citation statements)
references
References 19 publications
2
44
0
Order By: Relevance
“…3e,f). Interestingly, this value matches the 7.7‐nm spacing previously reported for the outer membrane porin protein layer using rotary shadowing studies (Steven et al ., 1977). We cannot determine at present whether this is merely a coincidence, or whether it implies some type of co‐registration between the peptidoglycan layer and the outer membrane layer.…”
Section: Resultsmentioning
confidence: 99%
“…3e,f). Interestingly, this value matches the 7.7‐nm spacing previously reported for the outer membrane porin protein layer using rotary shadowing studies (Steven et al ., 1977). We cannot determine at present whether this is merely a coincidence, or whether it implies some type of co‐registration between the peptidoglycan layer and the outer membrane layer.…”
Section: Resultsmentioning
confidence: 99%
“…It exhibits a 3-fold symmetry and triplet indentations penetrated by stain. These indentations were tentatively interpreted as membrane channels (Steven et al 1977). Evidence that matrix protein forms membranespanning pores was inferred from the higher permeability of wild type Salmonella typhimurium to the antibiotic cephaloridine compared to a mutant deficient in porin (Nikaido et al 1977).…”
Section: A)mentioning
confidence: 99%
“…Nikaido et al (1980) explained that diffusion channels in the outer membrane of intact cells, namely E. coli, had a diameter between 0.6 and 1.2 nm. In an early study, Steven et al (1977) showed that an E. coli porin revealed indentations with a diameter of 1.5-2 nm. When the NPs and bacteria are in contact, the NPs may plug the pores of the diffusion channels and prevent nutrition uptake.…”
Section: Preliminarily Proposed Killing Mechanismsmentioning
confidence: 99%